Acute Bone Marker Responses to Whole-Body Vibration and Resistance Exercise in Young Women - Sherk, Vanessa D. (2012)
Whole-body vibration (WBV) augments the musculoskeletal effects of resistance exercise (RE). However, its acute effects on bone turnover markers (BTM) have not been determined. This study examined BTM responses to acute high intensity RE and high intensity RE with WBV (WBV+RE) in young women (n=10) taking oral contraceptives in a randomized, cross-over repeated measures design. WBV+RE exposed subjects to 5 one-minute bouts of vibration (20 Hz, 3.38 peak–peak displacement, separated by 1 minute of rest) prior to RE. Fasting blood samples were obtained before (Pre), immediately post WBV (PostVib), immediately post RE (IP), and 30 minutes post RE (P30). Bone ALP did not change at any time point. TRAP5b significantly (p<0.05) increased from the Pre to PostVib, then decreased from IP to P30 for both conditions. CTX significantly decreased (p<0.05) from Pre to PostVib and from Pre to P30 only for WBV+RE. WBV+RE showed a greater decrease in CTX than RE (-12.6 ± 4.7% vs. -1.13 ± 3.5%). In conclusion, WBV was associated with acute decreases in CTX levels not elicited with resistance exercise alone in young women.